Peran Mediasi Person-Organizational Fit pada Pengaruh Responsible Leadership dan Knowledge Sharing - Noegroho, Andro Dewantara; Nurhayati; Salma Dian Latifah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This research seeks to examine the mediating role of Person-Organizational Fit (POF) in the relationship between Responsible Leadership (RL) and Knowledge Sharing (KS). Conducted as a quantitative study, it involved 70 members of the Management Student Association at Universitas Muhammadiyah Semarang and employed the Structural Equation Modeling - Partial Least Square (SEM-PLS) method. The results reveal that RL significantly and positively influences both POF and KS. Furthermore, POF acts as a mediator in the relationship between RL and KS, strengthening the effect of RL on knowledge-sharing behaviors. This study highlights the crucial role of responsible leadership and alignment of values between individuals and organizations in promoting collaboration and knowledge sharing, which are essential for achieving organizational competitive advantage.